The influence of LGBTQ celebrities on school youth’s perceptions of gender and sexual diversity - Botha, Tercia (University of the Free State, 2023)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 In recent times, South Africans have started to acknowledge and support counter-normative celebrities; celebrated Gay Pride Parades in cities such as Johannesburg and Cape Town; watched same-sex relationships on popular soap operas such as “Generations”; listened to music from counter-normative performers within the music industry and elected gay and lesbian members in the South African parliament. Role models such as celebrities, parents, teachers, and peers influence the attitudes and behaviours of teenagers and school youth. This can determine what kind of person they become, including their appearance, attitudes, gender and sexual diversity, and goals in life. A key aspect of identity development is the media, specifically social media, and television; hence, there is increasing concern that the youth learn more about gender and sexual diversity outside schools than in the formal curriculum. It is not surprising that the school youth are bound to look at LGBTQ celebrities in the media, in order to form their perceptions based on gender and sexual diversity. This research study explores the influence of LGBTQ celebrities on school youth’s perceptions of gender and sexual diversity. Using a case study methodology, semi-structured interviews were conducted with seven Grade 10 high-school learners studying at a co-ed high school in the Free State province of South Africa. Findings reveal that exposure to LGBTQ celebrities does influence their perceptions of gender and sexual diversity; the high-school learners expressed a need to be taught about gender and sexual diversity for their peers and teachers to have a better understanding; they revealed that they educate themselves on social media and learn more about gender and sexual diversity outside the schoolyard rather than in the formal curriculum; religion, culture and their parents also played a role in their perceptions of gender and sexual diversity. While the data is clear evidence of the influence of LGBTQ celebrities on their perceptions of gender and sexual diversity, it also revealed that the school youth realised the importance of being taught about gender and sexual diversity in the school system and they expressed a need to be taught for a better understanding. I conclude by calling on UMALUSI; the Department of Education; the Independent Examinations Board, and the South African Comprehensive Assessment Institute officials and inspectors of schools to pay regular visits to schools to ensure that the codes of conduct and policies are implemented thoroughly according to the South African Schools Act of 1996, the South African Constitution, and the Bill of Rights. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Onlangs het Suid-Afrikaners begin om teen-normatiewe bekendes te erken en te ondersteun; het Gay Pride-parades in stede soos Johannesburg en Kaapstad gevier; selfdegeslagverhoudings op gewilde sepies soos “Generations” gekyk; na musiek van teen-normatiewe kunstenaars in die musiekbedryf geluister en gay en lesbiese lede in die Suid-Afrikaanse parlement verkies. Rolmodelle soos bekendes, ouers, onderwysers en maats beïnvloed die houdings en gedrag van tieners en skooljeug. Dit kan bepaal watter mens hulle word, insluitend hul voorkoms, houdings, geslag en seksuele diversiteit en doelwitte in die lewe. ‘n Sleutelaspek van identiteitsontwikkeling is die media, spesifiek sosiale media, en televisie. Daarom is daar toenemende kommer dat die jeug meer oor geslag en seksuele diversiteit buite skole leer as in die formele kurrikulum. Dit is nie verbasend dat die skooljeug verplig is om na LGBTQ-bekendes in die media te kyk om hul persepsies op grond van geslag en seksuele diversiteit te vorm nie. Hierdie navorsingstudie ondersoek die invloed van LGBTQ-bekendes op skooljeug se persepsies van geslag en seksuele diversiteit. Deur gebruik te maak van ‘n gevallestudie metodologie, is semi-gestruktureerde onderhoude gevoer met sewe Graad 10 hoërskoolleerders wat aan ‘n gemengde hoërskool in die Vrystaatse provinsie van Suid-Afrika studeer. Bevindinge toon dat blootstelling aan LGBTQ-bekendes wel ‘n invloed het op hul persepsies van geslag en seksuele diversiteit; die hoërskoolleerders het ‘n behoefte uitgespreek om oor geslag en seksuele diversiteit geleer te word sodat hul maats en onderwysers ‘n beter begrip kan hê; hulle het onthul dat hulle hulself op sosiale media opvoed en meer leer oor geslag en seksuele diversiteit buite die skoolterrein as in die formele kurrikulum; godsdiens, kultuur en hul ouers het ook ‘n rol gespeel in hul persepsies van geslag en seksuele diversiteit. Terwyl die data duidelike bewyse toon van die invloed van LGBTQ-bekendes op hul persepsies van geslag en seksuele diversiteit, het dit ook aan die lig gebring dat die skooljeug besef het hoe belangrik dit is om oor geslag en seksuele diversiteit in die skoolkurrikulum geleer te word en hulle het ‘n behoefte uitgespreek om meer daaroor te leer vir beter begrip. Ek sluit af deur ‘n beroep op UMALUSI te doen; die Departement van Onderwys; die Onafhanklike Eksamenraad en die Suid-Afrikaanse Omvattende Assesseringsinstituut amptenare en inspekteurs van skole om gereelde besoeke aan skole te bring om te verseker dat die gedragskode en beleidsdokumente deeglik geïmplementeer word volgens die Suid-Afrikaanse Skolewet van 1996; die Suid-Afrikaanse Grondwet en die Handves van Menseregte. ___________________________________________________________________
Dissertation (M.Ed.(Psychology of Education))--University of the Free State, 2023
Keywords: LGBTQ celebrities; Role models; School youth; Identity development; Social media; Gender; Sexual diversity